Aqueous rechargeable zinc-manganese battery added with montmorillonite quasi-solid electrolyte and preparation method of aqueous rechargeable zinc-manganese battery
By using montmorillonite quasi-solid electrolyte in aqueous zinc ion batteries, the problems of zinc dendrites growth, hydrogen evolution and corrosion are solved, and the cycle stability and rate performance of the battery are significantly improved, and are suitable for large-scale energy storage.
Patent Information
- Application Number
- CN202411160760.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-22
AI Technical Summary
In practical applications, aqueous zinc ion batteries are limited by problems such as zinc dendrites growth, hydrogen evolution and corrosion, resulting in short battery cycle life, low Coulomb efficiency and reduced safety.
Using montmorillonite quasi-solid electrolyte, the gel-like electrolyte formed by dispersing the montmorillonite powder in the zinc brine solution and stirring it evenly, as the electrolyte material of the battery, to inhibit the growth of zinc dendrites, reduce the hydrogen evolution reaction and improve the rate performance. .
Effectively inhibit the growth of zinc dendrites, reduce hydrogen evolution reaction, improve rate performance, and effectively inhibit the corrosion of zinc negative electrodes, thereby improving the cycle stability and electrochemical performance of aqueous zinc ion batteries.
Smart Images

Figure CN119518130A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to an aqueous rechargeable zinc-manganese battery with montmorillonite quasi-solid electrolyte added thereto and a preparation method thereof. Background Art
[0002] Aqueous zinc-ion batteries (ZIBs) are considered to be a strong contender for the next generation of energy storage systems due to their high safety, low cost, and environmental friendliness, and have great application potential in the field of large-scale energy storage. However, the practical application of ZIBs is limited by problems such as zinc dendrite growth, hydrogen evolution, and corrosion, which can lead to short battery cycle life, low Coulombic efficiency, and reduced safety. In order to overcome these problems, researchers are committed to developing new electrolyte materials, among which quasi-solid electrolytes have attracted much attention because they combine the high ionic conductivity of aqueous electrolytes with the interfacial stability of solid electrolytes. Montmorillonite (Mont) is a natural layered silicate mineral with high specific surface area, good ion exchange capacity, excellent mechanical strength, and swelling properties, making it an ideal material for preparing quasi-solid electrolytes.
[0003] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0004] The main purpose of the present invention is to solve the problems existing in the above-mentioned background technology and to provide an aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte and a preparation method thereof.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A water-based rechargeable zinc-manganese battery with montmorillonite quasi-solid electrolyte comprises a positive electrode, a negative electrode, a separator and an electrolyte. The electrolyte is a montmorillonite quasi-solid electrolyte, which is a gel electrolyte formed by dispersing montmorillonite powder in a zinc salt aqueous solution and stirring it evenly.
[0007] Furthermore, the addition amount of the montmorillonite is 1% to 20% of the mass of the electrolyte.
[0008] Furthermore, the zinc salt is zinc sulfate, zinc nitrate, zinc chloride, zinc acetate or a mixture thereof.
[0009] Furthermore, the concentration of the zinc salt aqueous solution is 0.5-3M.
[0010] Furthermore, the material of the positive electrode comprises at least one additive, and the additive is selected from: carbon nanotubes, graphene, carbon fibers, metal oxides, conductive polymers or mixtures thereof.
[0011] Furthermore, the material of the negative electrode contains at least one additive, and the additive is selected from: bismuth, lead, indium, tin, antimony or a mixture thereof.
[0012] Furthermore, the separator is a cellulose separator, a glass fiber separator or a polymer separator.
[0013] A method for preparing an aqueous rechargeable zinc-manganese battery comprises the following steps:
[0014] (1) preparing a montmorillonite quasi-solid electrolyte: dispersing montmorillonite powder in a zinc salt aqueous solution and stirring to form a gel electrolyte;
[0015] (2) preparing a positive electrode;
[0016] (3) preparing a negative electrode;
[0017] (4) The prepared positive electrode, negative electrode and separator are stacked in sequence, injected with montmorillonite quasi-solid electrolyte, and packaged into a battery.
[0018] A montmorillonite quasi-solid electrolyte is a gel electrolyte formed by dispersing montmorillonite powder in a zinc salt aqueous solution and stirring the mixture evenly.
[0019] Furthermore, the addition amount of the montmorillonite is 1% to 20% of the mass of the electrolyte.
[0020] The present invention has the following beneficial effects:
[0021] The present invention provides a montmorillonite-based solid electrolyte and a preparation method and application thereof, which can effectively solve the problems of dendrite growth, hydrogen evolution and corrosion in aqueous zinc ion batteries, and improve the cycle stability and rate performance of the battery. The montmorillonite-based solid electrolyte of the present invention can effectively inhibit zinc dendrite growth, reduce hydrogen evolution reaction, improve rate performance, and effectively inhibit corrosion of zinc negative electrodes, thereby improving the performance of aqueous zinc ion batteries, has the advantages of low cost, simple preparation process, good safety performance, etc., is suitable for the field of large-scale energy storage, and has good application prospects.
[0022] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a Zn-Mont optical photograph of an embodiment of the present invention.
[0024] Figure 2 Structural characterization of Zn-Mont according to the embodiment of the present invention: (a) SEM and BET (inset); (b) SEM-Mapping; (c) XRD; (d) SEM-EDS.
[0025] Figure 3 Characteristics and structure of the Zn-Mont quasi-solid electrolyte of the embodiment of the present invention: (a) NMR spectrum; (b) FTIR spectrum; (c) Raman spectrum; (e) TGA curve; (f) MD and enlarged image of Zn-Mont-2 (g) MD and enlarged image of Zn-Mont-6.
[0026] Figure 4 Characterization of the side reactions of the zinc negative electrode of the embodiment of the present invention: (a) Tafel slope curve; (b) corresponding hydrogen evolution LSV curve; (c) corresponding oxygen evolution LSV; (d) XRD spectrum of the zinc negative electrode immersed in the electrolyte for 20 days; (eh) SEM and CLSM images of the zinc negative electrode immersed in ZSO and Zn-Mont electrolytes for 20 days, respectively.
[0027] Figure 5 SEM-Mapping and EDS of zinc negative electrode soaked in Zn-Mont for 20 days in the embodiment of the present invention
[0028] Figure 6 Electrochemical performance of the embodiments of the present invention: (a) CV of Zn||Ti half-cell; (b) Nyquist plot of Zn||Zn symmetric cell; (c) Nyquist plot of Zn||Zn symmetric cell; (d) voltage curve of Zn||Cu cell in ZSO electrolyte; (e) voltage curve of Zn||Cu cell in Zn-Mont electrolyte; (f) at 3 mA / cm 2 and 1mAh / cm 2 Coulombic efficiency of Zn||Cu battery at 0.5 and 5 mAh / cm 2 Long cycle performance under .
[0029] Figure 7 COMSOL simulation of zinc corrosion and hydrogen evolution reaction during zinc deposition / stripping process in the embodiment of the present invention.
[0030] Figure 8 Kinetic characteristics and morphology of Zn anode in ZSO and Zn-Mont electrolytes at different cycle numbers: (a) nucleation overpotential; (b) CA; (cd) XRD patterns of Zn anode after 20 and 50 cycles; (eh) CLSM and SEM images of Zn anode in different electrolytes after 20 and 50 cycles.
[0031] Fig. 9 SEM-Mapping and EDS after 50 cycles of ZSO.
[0032] Fig.10SEM-Mapping and EDS of the embodiment of the present invention after 50 cycles of Zn-Mont
[0033] Fig.11 Characterization of the positive electrode material prepared in the embodiment of the present invention and the performance of the Zn||MnOOH full battery: (a) SEM; (b) TEM; (c) CV; (d) rate; self-discharge (e) ZSO electrolyte; (f) Zn-Mont electrolyte; (g) long cycle of the full battery. DETAILED DESCRIPTION
[0034] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0035] The embodiment of the present invention provides a montmorillonite-based solid electrolyte, which is a gel electrolyte formed by dispersing montmorillonite powder in a zinc salt aqueous solution and stirring evenly. The electrolyte comprises montmorillonite, a zinc salt and water, and the amount of montmorillonite added is 1% to 20% of the mass of the electrolyte. Preferably, the mass fraction of montmorillonite is 2% to 10%. The mass fraction of montmorillonite is more preferably 4% to 8%. The zinc salt is selected from one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc acetate or a mixture thereof.
[0036] A method for preparing a montmorillonite-based solid electrolyte comprises the following steps:
[0037] a) adding montmorillonite powder into a zinc salt aqueous solution; preferably, the concentration of the zinc salt aqueous solution is 1 mol / L to 3 mol / L.
[0038] b) stirring the mixture obtained in step a) uniformly and allowing it to stand until a gel-like quasi-solid electrolyte is formed.
[0039] An aqueous zinc ion battery comprises: a zinc negative electrode, a positive electrode, a separator, and a montmorillonite-based solid electrolyte, wherein the montmorillonite quasi-solid electrolyte is a gel electrolyte formed by dispersing montmorillonite powder in a zinc salt aqueous solution and stirring evenly. The zinc ion battery is a zinc-manganese battery. The zinc salt is zinc sulfate, zinc nitrate, zinc chloride, zinc acetate or a mixture thereof. The concentration of the zinc salt aqueous solution is 0.5 to 3 M. The amount of montmorillonite added is 1% to 20% of the mass of the electrolyte. The positive electrode material is selected from one or more of manganese dioxide (MnO2), manganese hydroxide (MnOOH), vanadium oxide, Prussian blue analogues or a mixture thereof. The material of the positive electrode contains at least one additive, and the additive is selected from: carbon nanotubes, graphene, carbon fiber, metal oxide, conductive polymer or a mixture thereof. The material of the negative electrode contains at least one additive, and the additive is selected from: bismuth, lead, indium, tin, antimony or a mixture thereof. The separator is a cellulose separator, a glass fiber separator or a polymer separator.
[0040] The montmorillonite-based solid electrolyte of the present invention can effectively inhibit zinc dendrite growth, reduce hydrogen evolution reaction, improve rate performance, and effectively inhibit corrosion of the zinc negative electrode, thereby improving the performance of aqueous zinc ion batteries. It has the advantages of low cost, simple preparation process, good safety performance, etc., and is suitable for the field of large-scale energy storage.
[0041] The specific embodiments of the present invention are further described below.
[0042] Embodiment 1:
[0043] Preparation of Zn-Mont Quasi-Solid Electrolyte
[0044] 6 g of montmorillonite powder was added to 10 ml of 2 mol / L zinc sulfate aqueous solution and magnetically stirred for 30 min until the mixture was uniform.
[0045] The mixture obtained in step 1) was allowed to stand for 12 hours until a gel-like quasi-solid electrolyte was formed, which was recorded as Zn-Mont-6.
[0046] Embodiment 2:
[0047] Preparation of MnOOH cathode materials
[0048] Dissolve 0.01 mol potassium permanganate and 0.02 mol ammonium chloride in 100 ml of deionized water and stir well.
[0049] The solution obtained in step 1) was transferred to a 150 ml polytetrafluoroethylene-lined hydrothermal reactor and reacted at 160° C. for 12 hours.
[0050] After the reaction was completed, the reactor was naturally cooled to room temperature.
[0051] The product was filtered, washed with deionized water and ethanol several times, and then dried in vacuum at 60 °C for 12 h to obtain MnOOH powder.
[0052] Embodiment 3:
[0053] Assembly of aqueous zinc-ion batteries
[0054] MnOOH powder, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added to prepare a uniform slurry.
[0055] The slurry obtained in step 1) is uniformly coated on the aluminum foil current collector, and the MnOOH positive electrode is obtained after drying.
[0056] The zinc sheet was used as the negative electrode and the glass fiber separator was used as the separator. The positive electrode, the negative electrode and the separator were assembled into a CR2032 button battery.
[0057] The Zn-Mont-6 quasi-solid electrolyte prepared in Example 1 was injected into the battery.
[0058] Embodiment 4:
[0059] Electrochemical performance test of aqueous zinc-ion battery
[0060] The assembled aqueous zinc ion battery was subjected to the following electrochemical performance tests:
[0061] Cyclic voltammetry test: The scan rate was 0.1 mV / s.
[0062] Rate performance test: current densities are 0.5A / g, 1A / g, 2A / g and 5A / g respectively.
[0063] Cyclic performance test: current density is 1A / g, and cycle is 3000 times.
[0064] Effect of different montmorillonite contents on electrolyte performance
[0065] According to the method of Example 1, Zn-Mont quasi-solid electrolytes with montmorillonite mass fractions of 2%, 4%, 8% and 10% were prepared, respectively, and were recorded as Zn-Mont-2, Zn-Mont-4, Zn-Mont-8 and Zn-Mont-10.
[0066] According to the method of Example 3, aqueous zinc ion batteries using Zn-Mont quasi-solid electrolytes with different montmorillonite contents were assembled.
[0067] According to the method of Example 4, the effects of different montmorillonite contents on the electrochemical performance of the battery were tested.
[0068] Effects of different zinc salts on electrolyte performance
[0069] The Zn-Mont quasi-solid electrolyte was prepared according to the method of Example 1 using 2 mol / L aqueous zinc sulfate, zinc nitrate, zinc chloride and zinc acetate solutions, respectively.
[0070] According to the method of Example 3, aqueous zinc ion batteries using Zn-Mont quasi-solid electrolytes with different zinc salts were assembled.
[0071] According to the method of Example 4, the effects of different zinc salts on the electrochemical performance of the battery were tested.
[0072] Example 7: Inhibition of zinc negative electrode corrosion by Zn-Mont quasi-solid electrolyte
[0073] The zinc sheets were immersed in 2 mol / L zinc sulfate aqueous solution and Zn-Mont-6 quasi-solid electrolyte for 20 days, respectively.
[0074] The corrosion condition of the zinc sheet surface was observed, and the morphology of the zinc sheet surface was characterized using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM).
[0075] Results Analysis
[0076] The results of electrochemical performance tests show that the cycle stability and rate performance of zinc ion batteries using Zn-Mont-6 quasi-solid electrolyte are significantly improved compared with batteries using 2 mol / L zinc sulfate aqueous solution as electrolyte. The results of electrochemical performance tests show that with the increase of montmorillonite content, the cycle stability and rate performance of aqueous zinc ion batteries show a trend of first increasing and then decreasing. Zn-Mont-6 quasi-solid electrolyte exhibits the best comprehensive performance. The results of electrochemical performance tests show that Zn-Mont quasi-solid electrolytes prepared using different zinc salts have a certain effect on the electrochemical performance of aqueous zinc ion batteries. Among them, Zn-Mont quasi-solid electrolytes prepared using zinc sulfate exhibit the best comprehensive performance. Obvious corrosion pits and cracks appear on the surface of zinc sheets immersed in 2 mol / L zinc sulfate aqueous solution, while the surface of zinc sheets immersed in Zn-Mont-6 quasi-solid electrolyte is smooth and flat, with no obvious corrosion. The results of SEM and CLSM further confirm that Zn-Mont-6 quasi-solid electrolyte has a good protective effect on zinc negative electrode. The montmorillonite-based solid electrolyte and the preparation method thereof provided by the present invention are simple and easy to operate, low in cost, can effectively inhibit zinc dendrite growth, reduce hydrogen evolution reaction, improve rate performance, and effectively inhibit corrosion of the zinc negative electrode, thereby improving the performance of aqueous zinc ion batteries, and have good application prospects.
[0077] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A water-based rechargeable zinc-manganese battery with montmorillonite quasi-solid electrolyte, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The electrolyte is a montmorillonite quasi-solid electrolyte, and the montmorillonite quasi-solid electrolyte is a gel electrolyte formed by dispersing montmorillonite powder in a zinc salt aqueous solution and stirring the mixture evenly.
2. The aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte according to claim 1, characterized in that: The added amount of the montmorillonite is 1% to 20% of the mass of the electrolyte.
3. The aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte according to claim 1 or 2, characterized in that: The zinc salt is zinc sulfate, zinc nitrate, zinc chloride, zinc acetate or a mixture thereof.
4. The aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte according to any one of claims 1 to 3, characterized in that: The concentration of the zinc salt aqueous solution is 0.5-3M.
5. The aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte according to any one of claims 1 to 4, characterized in that: The material of the positive electrode comprises at least one additive, and the additive is selected from: carbon nanotubes, graphene, carbon fibers, metal oxides, conductive polymers or mixtures thereof.
6. The aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte according to any one of claims 1 to 5, characterized in that: The material of the negative electrode comprises at least one additive, and the additive is selected from: bismuth, lead, indium, tin, antimony or a mixture thereof.
7. The aqueous rechargeable zinc-manganese battery with added montmorillonite quasi-solid electrolyte according to any one of claims 1 to 6, characterized in that: The separator is a cellulose separator, a glass fiber separator or a polymer separator.
8. A method for preparing an aqueous rechargeable zinc-manganese battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) preparing a montmorillonite quasi-solid electrolyte: dispersing montmorillonite powder in a zinc salt aqueous solution and stirring to form a gel electrolyte; (2) preparing a positive electrode; (3) preparing a negative electrode; (4) The prepared positive electrode, negative electrode and separator are stacked in sequence, injected with montmorillonite quasi-solid electrolyte, and packaged into a battery.
9. A montmorillonite quasi-solid electrolyte, characterized in that: The montmorillonite powder is dispersed in a zinc salt aqueous solution and stirred evenly to form a gel electrolyte.
10. The montmorillonite quasi-solid electrolyte according to claim 9, characterized in that: The added amount of the montmorillonite is 1% to 20% of the mass of the electrolyte.
Citation Information
Patent Citations
Quasi-solid electrolyte with wide working temperature range and supercapacitor
CN113782347A
Quasi-solid electrolyte of aqueous zinc ion battery as well as preparation method and application of quasi-solid electrolyte
CN115020827A
Multi-component mixed electrolyte as well as preparation method and application thereof
CN115441067A
Mixed-state electrolyte of aqueous zinc ion battery
CN118367237A
Cited By
Aqueous zinc-manganese battery, electrolyte, preparation and application
CN120600949A
